Femtosecond Laser Fabricated Ag@Au and Cu@Au Alloy Nanoparticles for Surface Enhanced Raman Spectroscopy Based Trace Explosives Detection - Sree Satya Bharati, Moram; Byram, Chandu; Soma, Venugopal R. (Frontiers in Physics, 2018)
Herein we present results from our detailed studies on the fabrication of Ag@Au and Cu@Au alloy nanoparticles (NPs) using the femtosecond laser ablation in liquid technique. The NPs were obtained by ablating the pure Ag, Cu targets (bulk) in HAuCl4 (5 mM) solution. The absorption properties of the obtained NPs colloids were characterized using UV-Visible absorption spectrometer and their size, shape, and crystallinity were investigated using the XRD, FESEM and TEM techniques. The fabricated NPs were utilized for sensing of explosive molecules such as 2, 4, 6-trinitrophenol (PA), 2, 4-dinitrotoluene (DNT) and a common dye methylene blue (MB) using the surface enhanced Raman spectroscopy (SERS) technique. The detection limit in terms of weight was as low as few nano-grams in the case of nitroaromatic explosive compounds (PA, DNT) and few picograms in the case of a common dye molecule (MB). Typical enhancement factors achieved were estimated to be 104, 105 and 107, respectively, for PA, DNT, and MB. The significance of the present work lies in exploring the performance of the prepared NPs being used as SERS substrates for explosives detection using a portable Raman instrument. Such capability enables one to carry the spectrometer to the point of interest in the field and evaluate any hazardous samples within a short period of time.